Implementasi Nilai-nilai Filsafat Pendidikan dalam Mengemban Tugas Secara Profesional pada Guru Sekolah Dasar - Muhammad Azhar Nawawi; Arita Marini; Edwita Edwita; Durotul Yatimah; Linda Zakiah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study examines the implementation of educational philosophy values in carrying out professional duties in elementary school teachers in Jabodetabek. Teacher professionalism has an important role in the success of student learning. For this reason, teachers are required to be able to uphold and implement their professionalism as an educator. This study uses a quantitative approach. Data collection used random sampling techniques in the form of a questionnaire with a Likert scale model. Data collection was carried out online through the GoogleForm container from September-November, Data analysis uses descriptive statistical techniques. The results of the research conducted show that from the survey questionnaire data on the implementation of the values of the philosophy of education towards professionalism in carrying out tasks for elementary school teachers, with a sample of 88 teachers, with two indicators of professionalism and a code of ethics as a reference, it shows an attitude of professionalism in the moderate category with the percentage shown from each indicator with the highest percentage scale is 100%, namely in terms of professionalism showing a percentage of professionalism with a moderate category of 54.7%, in terms of the code of ethics showing a percentage of professionalism with a moderate category of 57%. Thus, based on the data findings related to the implementation of the values of the philosophy of education towards professionalism in carrying out tasks for elementary school teachers, it shows an attitude of professionalism in the moderate category. This shows that there is a need to increase motivation for teachers in an effort to implement professionalism through internalizing the values of philosophy of education as a guide to teacher professionalism, both in the form of teacher coaching programs and teacher leadership training.